2016
DOI: 10.1007/s00213-016-4308-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intranasal oxytocin in opioid-dependent individuals and healthy control subjects: a pilot study

Abstract: Methadone Oxytocin Option. ClinicalTrials.gov identifier: NCT01728909.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Furthermore, a single dose of intranasal oxytocin application was not successful in reducing opioid craving [38]. Our findings suggested that the interaction between oxytocin and craving is complicated, and personality traits (novelty-seeking) might play roles as mediating or modulating variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a single dose of intranasal oxytocin application was not successful in reducing opioid craving [38]. Our findings suggested that the interaction between oxytocin and craving is complicated, and personality traits (novelty-seeking) might play roles as mediating or modulating variables.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of intranasal oxytocin did not reduce cue-induced opioid craving [38]; however, a different 2-week trial indicated that intranasal oxytocin suppressed heroin craving [39]. A recent study demonstrated an unexpectedly higher level of oxytocin among abstinent heroin addicts than controls [40].…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized, double‐blind, placebo‐controlled, crossover study, Woolley et al . () reported that intranasal OT administration (40 IU) did not improve cue‐induced craving in opioid‐dependent subjects receiving opioid replacement therapy. In contrast, in a placebo‐controlled trial of individuals undergoing methadone replacement treatment for opioid and co‐occurring cocaine use disorder, placebo‐treated patients reported an increase for heroin craving, while individuals who received intranasal OT treatment (40 IU; two times daily × 2 weeks) did not exhibit increased craving response (Stauffer et al , ), providing some promise for the treatment of this population.…”
Section: Effects Of Opioid Addiction On the Oxytocinergic Systemmentioning
confidence: 99%
“…There is currently a limited number of clinical trials investigating the efficacy of OT in the treatment of drug addiction. With regards to opioid addiction, there have been only two clinical studies to‐date that assessed the effects of intranasal OT on opioid‐dependent patients (Stauffer et al , ; Woolley et al , ). The main outcome of both studies demonstrates a safe and good tolerability profile of OT administration in opioid‐dependent individuals, even after repeated administration for 2 weeks.…”
Section: Effects Of Opioid Addiction On the Oxytocinergic Systemmentioning
confidence: 99%
“…A growing number of trials are exploring intranasal oxytocin as a potential drug in the treatment of alcohol use disorder and substance abuse, yet so far with mixed results [13][14][15][16][17]. One pilot trial suggested that the anxiolytic effects of intranasal oxytocin may be favorable in reducing alcohol withdrawal symptoms [18].…”
Section: Introductionmentioning
confidence: 99%